2016
DOI: 10.1002/jor.23326
|View full text |Cite
|
Sign up to set email alerts
|

CD146 defines commitment of cultured annulus fibrosus cells to express a contractile phenotype

Abstract: Characterization of cells is important for facilitating cell-based therapies for degenerative diseases of intervertebral discs. For this purpose, we analyzed mouse annulus fibrosus cells by flowcytometory to detect phenotypic change in their primary cultures. After examination of sixteen cell surface proteins, we focused on CD146 that solely increased during culture expansion. CD146 is known to be a marker for mesenchymal stem cells and for their vascular smooth muscle commitment with expression of contractile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 50 publications
4
45
0
Order By: Relevance
“…In recent years, functional cellular markers for AF cells, such as CD146 and Mohawk have been identified, offering opportunities for AF cell repair. Despite the many studies that have been performed on transplanting cells to AF, no definitive transplantation methods have been established .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, functional cellular markers for AF cells, such as CD146 and Mohawk have been identified, offering opportunities for AF cell repair. Despite the many studies that have been performed on transplanting cells to AF, no definitive transplantation methods have been established .…”
Section: Discussionmentioning
confidence: 99%
“…Schematics and representative microscopic images of the different cell types and their locations in the healthy adult AF. (A) Peripheral cells, (B) outer annulocytes, (C) inner annulocytes, and (D) interlamellar cells …”
Section: Cells Of the Annulus Fibrosusmentioning
confidence: 99%
“…A single layer of cells expressing the markers CD146 and transgelin (SM22ɑ) was identified in the AF periphery in both mouse and human IVD (Table ) . While there is speculation that these CD146 + cells may be a population of resident stem cells, their function is still not clear, and they may also serve important functions in wound healing responses and contractility …”
Section: Cells Of the Annulus Fibrosusmentioning
confidence: 99%
“…In terms of AF repair, the lack of specific markers for functional AF cells has hampered similar developments. Recently, new markers such as CD146 and Mohawk (MKX) have been identified that characterize the functional AF cell phenotype, opening the door for future cell engineering approaches. Notably these technologies may represent new strategies for unlimited generation of functional IVD‐like cells; though in vivo studies will be needed to assess the therapeutic values of cell engineering developments for IVD repair and regeneration.…”
Section: Function Vs Mimics: Biomaterials and Cell Engineeringmentioning
confidence: 99%